Perfil clínico, epidemiológico e laboratorial de crianças com leishmaniose visceral, internadas no Hospital Universitário João De Barros Barreto, no período de janeiro de 1993 a dezembro de 2003 - ALMEIDA, Augusto Cesar Costa De (2022)
The epidemiological data of visceral leishmaniasis in the state of Pará, in the last few years, demonstrated that all the work developed by the authorities was not efficient enough to avoid the increase of the disease, leading to believe that the used measures were not as effective as expected. Knowing that pediatric population represent the majority of the cases of visceral leishmaniasis and that this illness is potentially serious if it was not appropriately treated or if it is done with delay, it makes necessary to trace the clinical and epidemiological profile of the sick children in our region, to make early diagnosis, decreasing the morbidity and the mortality of the disease. Based on this information, was made an observational, transversal and retrospective studied, which analyzed the medical handbooks of interned patients in Hospital Universitário João de Barros Barreto, in the period between january of 1993 and december of 2003. Took part in the study 252 patients, who ranged in age from 0 to 12 years old, came exclusively from cities of Pará (regional cases) and who had the diagnosis of visceral leishmaniasis described on the leaving hospital summary. In this study was observed that the male was the majority (58,7%) and the most prevalent age group was 1-4 years old (69%). The city which had more numbers of cases was Mocajuba with 25 patients (9,92%). In this casuistic was verified that 69% presented a disease duration of 2 months or more, at the moment of admission. The clinical findings that prevailed in more than 90% of the cases were distension of the abdomen, hepatomegaly, splenomegaly, fever and paleness. The enlargement of liver and spleen was relationed with the duration of the disease, being the hepatomegaly observed in a higher frequency than the splenomegaly in this study. Infectious complications notified in 105 patients (41,66%), between than, pneumonia was the most common infection, in our patients (29,36%). The most common hematological disturbance was the anemia, present in 92,06% of all the cases. The lethality rate observed in our study was 3,17%, being infections and bleeding diathesis the complications strengthly associated with death. This study alerts about the necessity of knowing the clinical and epidemiological features of visceral leishmaniasis in Pará state, specially in the recognition of severe or complicated cases, to offer a correct diagnosis and an early and apropos treatment.